Snowball Throwing Method: Peningkatan Hasil Belajar pada Materi Zaman Pra Aksara di SMK Negeri Purwosari - Agni, Daeng Galuh Puspita; Haryudo, Subuh Isnur (Jurnal Pendidikan Madrasah, 2024)
This research aims to improve student learning outcomes using a cooperative learning method with a snowball throwing model. This study uses the classroom action research method with qualitative descriptive analysis. Data is collected through observation, documentation, and reflection. The subject of the study was a student of class X Rpl A at SMK Negeri Purwosari. The results showed that cooperative learning using the snowball throwing model could increase learning outcomes by 22% from an average of 54.2 to 66.2. This learning can also increase student activity by 53%. The snowball throwing model can also train students' leadership potential, skills, and creativity.